Endoscopic Retrograde Cholangiopancreatography–Associated AmpC Escherichia coli Outbreak. (30th March 2015) - Wendorf, Kristen A.; Kay, Meagan; Baliga, Christopher; Weissman, Scott J.; Gluck, Michael; Verma, Punam; D'Angeli, Marisa; Swoveland, Jennifer; Kang, Mi-Gyeong; Eckmann, Kaye; Ross, Andrew S.; Duchin, Jeffrey
<x content-type="archive" xml:space="preserve">Abstract</x> BACKGROUND We identified an outbreak of AmpC–producing Escherichia coli infections resistant to third-generation cephalosporins and carbapenems (CR) among 7 patients who had undergone endoscopic retrograde cholangiopancreatography at hospital A during November 2012–August 2013. Gene sequencing revealed a shared novel mutation in a blaCMY gene and a distinctive fumC/ fimH typing profile. OBJECTIVE To determine the extent and epidemiologic characteristics of the outbreak, identify potential sources of transmission, design and implement infection control measures, and determine the association between the CR E. coli and AmpC E. coli circulating at hospital A. METHODS We reviewed laboratory, medical, and endoscopy reports, and endoscope reprocessing procedures. We obtained cultures from endoscopes after reprocessing as well as environmental samples and conducted pulsed-field gel electrophoresis and gene sequencing on phenotypic AmpC isolates from patients and endoscopes. Cases were those infected with phenotypic AmpC isolates (both carbapenem-susceptible and CR) and identical blaCMY-2, fumC, and fimH alleles or related pulsed-field gel electrophoresis patterns. RESULTS Thirty-five of 49 AmpC E. coli tested met the case definition, including all CR isolates. All cases had complicated biliary disease and had undergone at least 1 endoscopic retrograde cholangiopancreatography at hospital A. Mortality at 30 days was 16% for all patients and 56% for CR patients. Two of 8 reprocessed endoscopic retrograde cholangiopancreatography scopes harbored AmpC that matched case isolates by pulsed-field gel electrophoresis. Environmental cultures were negative. No breaches in infection control were identified. Endoscopic reprocessing exceeded manufacturer's recommended cleaning guidelines. CONCLUSION Recommended reprocessing guidelines are not sufficient. Infect Control Hosp Epidemiol 2015;00(0): 1–9